Reduced Visual Event-Related Delta Oscillatory Responses in Amnestic Mild Cognitive Impairment - Yener, Görsev; Kurt, Pınar; Emek Savaş, Derya Durusu; Güntekin, Bahar; BAŞAR, EROL (Ios Press, Nieuwe Hemweg 6B, 1013 Bg Amsterdam, Netherlands, 2013)
Mild cognitive impairment (MCI) is considered as a prodromal stage for Alzheimer's disease (AD) in the majority of cases. Event-related oscillations might be used for detection of cognitive deficits. Our group's earlier results showed diminished delta visual and auditory target oscillatory responses in AD, and we investigated whether this prevails for MCI. Eighteen MCI subjects and 18 age-matched healthy elderly controls were investigated. The maximum peak-to-peak amplitudes of oscillatory responses for each subject's averaged oscillatory target responses in delta, theta, and alpha frequency bands upon application of visual oddball paradigm were measured. Repeated measures of ANOVA was used to analyze four locations (frontal, central, parietal, occipital), at three coronal (left, midline, right) sites. Independent t tests were applied for post-hoc analyses. The oddball target delta response (0.5-3.0 Hz) was 26-32% lower in MCI than healthy controls over fronto-central-parietal regions [F(1.34) = 4.562, p = 0.04]. Without a group effect, theta oscillatory responses (4-7 Hz) showed significant differences in coronal electrodes indicating highest values over mid-electrode sites, and a anteriorposterior x coronal effect, being maximum at mid-central. Alpha frequency band analyses indicated no statistical differences. Peak-to-peak amplitudes of visual target delta oscillatory responses were lower in fronto-central-parietal regions in MCI than in healthy controls. This supports our earlier findings in AD, showing hypoactive delta fronto-central-parietal regions during cognitive tasks. These results indicate that event-related oscillations may detect early changes of brain dynamics in MCI, and deserves to be investigated as a candidate biomarker in further studies using multimodal techniques.
Keywords: Biomarker; early diagnosis of Alzheimer's disease; electroencephalographic rhythms; event-related potentials; mild cognitive impairment; oscillations; Alzheimers-Disease; Theta-Oscillations; Brain; Rhythms; Eeg; Synchronization; Diagnosis; Cortex; Electroencephalography; Excitability